A study on attitude towards internet advertising among non-technical department employees of Petronas Carigali Sdn Bhd Sarawak operations / Awangku Mohd Hazriq Fadzly Awg Ahmad - Awg Ahmad, Awangku Mohd Hazriq Fadzly (Faculty of Business and Management, UiTM Sarawak, 2015)
The size and range of online advertisement is increasing dramatically. Businesses are spending more on internet advertisement than before. Understanding the factors that influence internet advertisement effectiveness is crucial. The number of Internet users around the world including in Malaysia are increasing. Thus, the advertising agency and the marketer need to understand the consumers' attitude towards internet advertising in order to build effective internet advertising. In this research, the four independent variables that the researcher evaluate are consists of credibility, informative, hedonic/pleasure, and irritation that will impact on dependent variable of consumers' attitude toward internet advertising By using the Statistical Packages for Social Science (SPSS) version 22.0 to analyze 120 sets of questionnaires collected from the respondents, researchers found that all the variables which credibility, informative, hedonic/pleasure and irritation are significant related to consumers' attitude towards internet advertising. Among the independent variables, hedonic/pleasure has the strongest significant relationship with dependent variable consumers' attitude towards internet advertising. The target population in this research study are the Non-Technical Department Employees of Petronas Carigali Sdn Bhd Sarawak Operations who is also an internet user who might have possibility exposure to internet advertising. The sampling frame comprises internet users (Non-Technical department Employees) with the criteria of frequency click on internet advertisement is at least one and the hours per week spend online is at least five hours. The limitations and recommendations are discussed with regards to further improvement.